STEEL CASTING DESIGN ON CAM SPROCKET USING MAGMASOFT COMPUTER SIMULATION - ACHYARSYAH , MOCHAMAD
A new methodology in steel casting production process has been developed to measure the level of shrinkage porosity defect occurred through casting simulation predictions. Steel casting, which has a relatively heavy section, need a further consideration on its feeder design, particularly in its number, location, size, and dimension. Some table and graphics applications and casting design guidelines give some different results each other and not all resulting a sound casting. A more complex dimension will result solidification time and direction that did not explain by any other formula, and furthermore Chvorinov formula is not applicable to any further extent since it is only valid to plate, bar, and sphere shapes. A casting simulation program gives a fine solution in calculating solidification time and gives several analyses. The operating of this casting simulation can influence some casting design performance significantly. The most important thing in applications this casting simulation is gaining a “cold trial and error”, and of course, this is more efficient in both time and cost production in a long term. This thesis describe how to risering steel casting using the casting simulation program which is Cam Sprocket is the object of this research. Former design, D1, is made and trialed using some manual calculation, table, literature, and without using casting simulation program. A shrinkage cavity occurred on the casting in the interface of feeder neck and casting The result of simulation program application using casting data and design shows the relatively similar to that in trial process. Position, shape and size of the shrinkage porosity remain the same. Design and calculation remedy has been done and simulated until sound casting produced and gaining a higher yield for the need of effectivity and efficiency.